2007
DOI: 10.1016/j.juro.2007.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Oxalate and Calcium Oxalate Nephrolithiasis

Abstract: Dietary sources of oxalate can induce hyperoxaluria and crystal deposition in the kidneys with associated degradation in renal biology. Eliminating oxalate from the diet decreases not only urinary oxalate, but also calcium oxalate crystal deposits in the kidneys and improves their function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 20 publications
0
25
1
2
Order By: Relevance
“…From the above discussion, one can conclude that under normal conditions, crystals do not adhere to renal tubular epithelial cells and are readily excreted in the urine. However, with antecedent renal tubular epithelial damage and during the process of renal tubular repair,144146 specific crystal-binding proteins are expressed at the apical surface of the renal epithelial cell, predisposing crystal adhesion and possibly stone formation. Whether this process has a pathogenic function in many clinical conditions associated with tubular nephrocalcinosis and nephrolithiasis deserves intense future investigation 130…”
Section: The Role Of Renal Tubular Crystal Retentionmentioning
confidence: 99%
“…From the above discussion, one can conclude that under normal conditions, crystals do not adhere to renal tubular epithelial cells and are readily excreted in the urine. However, with antecedent renal tubular epithelial damage and during the process of renal tubular repair,144146 specific crystal-binding proteins are expressed at the apical surface of the renal epithelial cell, predisposing crystal adhesion and possibly stone formation. Whether this process has a pathogenic function in many clinical conditions associated with tubular nephrocalcinosis and nephrolithiasis deserves intense future investigation 130…”
Section: The Role Of Renal Tubular Crystal Retentionmentioning
confidence: 99%
“…Calcium oxalate is the most common constituent of urinary stones in animal model of the urolithiasis which has been established by means of feeding Hyp, an endogenous precursor of oxalate (Khan et al, 2007). They reported that rats receiving Hyp for 42 days showed hyperoxaluria, calcium oxalate crystalluria and nephrolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Batas aman konsumsi kalsium oksalat bagi orang dewasa adalah 0.60-1.25 g per hari selama 6 minggu berturut-turut (Khan et al, 2007;Knudsen et al, 2008;Bazin et al, 2016;Bong et al, 2017;Siener et al, 2017;). Untuk itu, perlu dilakukan proses reduksi oksalat pada umbi kimpul agar selanjutnya dapat dikonsumsi tanpa menimbulkan rasa gatal dan juga aman bagi tubuh tanpa memberikan efek negatif terhadap kesehatan.…”
Section: Kadar Kalsium Oksalat Pada Umbi Kimpul Sebelum Dan Setelah Punclassified